2008
DOI: 10.1007/s11104-008-9665-6
|View full text |Cite
|
Sign up to set email alerts
|

Legume defoliation affects rhizosphere decomposers, but not the uptake of organic matter N by a neighbouring grass

Abstract: Legume-grass interactions have a great influence on grassland primary production and it was recently shown how defoliation of a legume can increase the transfer of fixed N to a neighbouring grass. It has also been shown that defoliation of a plant can increase soil microbial activity and lead to better soil N availability in the rhizosphere of the defoliated plant. We combined these two perspectives and tested whether defoliation of a legume (Lotus corniculatus) can enhance N nutrition of the neighbouring gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Similarly, soil microbial activity should be strongly coupled to both leaf trait and plant growth responses, and promoted by nonnative and N-fixing species (Wardle et al 2004, Reinhart and Callaway 2006, De Deyn et al 2008, Peltzer et al 2009, Orwin et al 2010. Consistent with these expectations, we found that soil microbial activity was stimulated particularly by nonnative N-fixing plant species on fertile soils or with defoliation, but did not determine the belowground mechanisms involved (Bardgett and Wardle 2003, Ayres et al 2007, van der Putten et al 2007, Saj 2008.…”
Section: Do Soil Fertility and Disturbance Interact To Control Plant supporting
confidence: 76%
“…Similarly, soil microbial activity should be strongly coupled to both leaf trait and plant growth responses, and promoted by nonnative and N-fixing species (Wardle et al 2004, Reinhart and Callaway 2006, De Deyn et al 2008, Peltzer et al 2009, Orwin et al 2010. Consistent with these expectations, we found that soil microbial activity was stimulated particularly by nonnative N-fixing plant species on fertile soils or with defoliation, but did not determine the belowground mechanisms involved (Bardgett and Wardle 2003, Ayres et al 2007, van der Putten et al 2007, Saj 2008.…”
Section: Do Soil Fertility and Disturbance Interact To Control Plant supporting
confidence: 76%
“…This indicates likely differences in the consequences of defoliating woody versus herbaceous plants. In that light, most previous studies showing a positive effect of defoliation on N availability have involved grassland plants (Mikola et al 2005, Ayres et al 2007, Hamilton et al 2008, Saj et al 2008), but not woody plants (Pastor et al 1993, Stark et al 2000, Harrison and Bardgett 2004). While it could be predicted that Carmichaelia may have positive effects on neighbouring plants through enhancing soil N status (Bellingham et al 2001), our results reveal that this is more than offset by a net negative competitive effect which is reversible only by substantial defoliation (Del‐Val and Crawley 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is that these organisms are abundant in the rhizosphere and thus are directly affected by plant roots (Clarholm 1985;Griffiths 1994). They also have high turnover rates and can respond to changes in resource availability within a few days (Bazot et al 2005;Mikola et al 2005;Saj et al 2008), which allows examination of plant-soil feedbacks in a short temporal scale (Hamilton and Frank 2001). It is, however, possible that the effects of changes in micro-food web structure on litter-N availability were outweighed by the effects of changes in the abundance of bigger organisms, such as enchytraeids and microarthropods, although populations of these animals should be less able to respond to changes in resource availability in the time scale of our study.…”
Section: Litter Effects On Decomposers and Plant N Uptakementioning
confidence: 99%